Men’s and Women’s Language Features Used in the Conversation of the Talk Show “The Ellen Show” - Dinata, Adriel Elbert; Ni Wayan Sukarini; Sang Ayu Isnu Maharani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This article is entitled Men’s and Women’s Language Features Used in the Conversation of the Talk Show “The Ellen Show”. This article aims to find the men’s and women’s language features in “The Ellen Show”. The analysis of the article was focused on the utterance of man speakers and woman speakers to find out the features of men’s and woman’s language used in a conversation on a talk show. This article uses Lakoff’s theory about Women’s Language Features and Coates’ theory about Men’s Language Features to analyse the utterances of the talk show’s men and women speakers. This article uses the documentation and observation technique to collect data. As a result, there are ten data and seven language features from woman speakers, namely Lexical Hedges or Filters, ‘Empty’ Adjectives, Rising Intonation on Declarative, Intensifies, ‘Super-polite’ Forms, Avoidance of Strong Swear Words, and Empathic Stress. From the man speaker, there are six data and four language features: Direct Form, Compliment, Swearing, Taboo Language, and Questions. The results indicate any linguistic features, differences, and similarities between men and women in a conversation on the talk show.